The Cost of Childhood Respiratory Illness: The Primary and Secondary Care Interface - Cropper, JA (Prim Care Respir J, 2001)
INTRODUCTION: Although the prevalence of asthma has increased over the past two decades, there is no comprehensive method for calculating the financial cost of the condition to include both primary and secondary sectors. OBJECTIVE: To quantify the cost of healthcare provision in primary and secondary care in relation to respiratory illness. METHODS: A sample of children (n=713) was randomly selected from respondents to a postal respiratory questionnaire sent out to two general practice populations in 1993. The selected children were stratified according to responses to five key questions on the questionnaire. An increasing number of positive responses to the key questions indicated an increasing likelihood of asthma. Details of all the children's primary and secondary care utilisation over a two-year period were obtained from general practice records. A method was then established to calculate unit costs for all aspects of primary and secondary care, which were then applied to the utilisation data. RESULTS: The cost of healthcare provision in both primary and secondary care increased as the children's likelihood of asthma increased, with a statistically significant linear trend (p<0.05). The majority of care was provided in primary care for both respiratory and non-respiratory illness, however, the majority of cost was located in secondary care. The ‘likely asthmatics’ accounted for a greater proportion of the total cost of care (61%) than the ‘unlikely asthmatics’. CONCLUSIONS/RECOMMENDATIONS: The findings of this study have relevance for both primary and secondary care, as have the established unit costs; in providing information for resource allocation decisions.